Do Socio-Economic Indicators Associate with Covid-2019 Cases? Findings from a Philippine Study - Mark Alipio; Grace Meroflor Lantajo (IMCC Journal of Science, 2021)
In this study, seven socio-economic indicators were associated with Covid-2019 cases across 17 regions in the Philippines. The number of Covid-2019 cases as of April 7, 2020, was considered for the analysis. Descriptive statistics, Kendall rank correlation, and stepwise regression were used to determine if the seven socio-economic indicators were associated with Covid-2019 cases. No significant associations were noted in both magnitudes of poor families and subsistence poor population, and savings to Covid-2019 cases. However, high income and low subsistence incidence were associated with significant reductions in Covid-2019 cases across the 17 regions of the Philippines. The result of the study provides additional knowledge to policy makers and health officials in formulating targeted strategies to regions that could potentially record high number of Covid-2019 cases in the future. Given the seasonal and recurring nature of Covid-2019 with respect to previous outbreaks, it is essential for the Philippine government to create directed policies and innovate programs that would decrease subsistence and increase income. Concerted multi-region efforts should be made to prepare for possible infection outbreaks in the future.
Keywords: H75; I15; I18; I12; 330; Covid-2019; income; poverty; socio-economic; subsistence